Case Report: Multisystemic life-threatening gunshot injuries in an adult Vizsla dog - Gremillet, Bérengère Cyrielle Hadrienne; Troussier, Geoffrey; Serlenga, Lucia (Frontiers in Veterinary Science, 2026)
An 8-year-old male Vizsla dog was presented to the emergency and critical care unit due to polytraumatic injuries from a rifle shot. Multimodal diagnostic imaging revealed life-threatening injuries affecting the cardiovascular, respiratory, and gastrointestinal systems. Less severe injuries to the left kidney and retained pellets in the peritoneum and musculoskeletal system were also identified. Lesion triage and targeted treatment—including emergency stabilization, thoracotomy (subtotal pericardiectomy), and abdominal laparotomy (enterotomies and gastrotomy)—combined with tailored medical management resulted in dog’s full recovery.